COMPARISON OF LINEAR AND ANGULAR MEASUREMENTS OF THE SCULL WITH USING DIFFERENT BASE POINTS - Fedoryshcheva, V.O.; Yabluchansky, М.І.; Arnold, W.; Naumova, E.O. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
It was the aim of this study to compare two different methods of linear and angular craniometric measurements of the neuro- and viscerocranium. Of 38 normal skulls of adult individuals from Verhnij Saltovskij moglinik lateral x-rays were taken with a PYM-20 x-ray machine at 40-45 kV electron beam and an exposure time between 0.1 to0.2 sec. As base points for the measurements served either the center of the sella turcica (point S), or the back edge of the tuberculum sellae (point S’). Linear and angular marks were measured between the following points: Ba, B, L, N, O, Or, Pr, S, S', Fca. The mean value (M, cm), standard quadratic deviation (sd) were determined. Statistical analysis between groups was carried out using the Mann-Whitney test. The results showed distinct differences between linear and angular measurements using the different base points. It is concluded that in anthropological research for craniometric measurements the internationally recommended S point as standard base point should be used.